STRUCTURE AND MORPHOLOGY ANALYSIS OF ANNEALING POST-TREATMENT THIN FILM TITANIUM AND COPPER-DOPED ZINC OXIDE - Astuti, Budi; Abidah, Niswatul; Fatiha, Egy Awalia; Ardi Nugraha, Krisna (Universitas Mataram, 2023)
Ti-Cu doped ZnO thin film has been successfully deposited on a preparate glass substrate using the spin coating method with post-treatment annealing temperatures of 350oC - 550oC. This research analyzes the structure and morphology of Ti-Cu doped ZnO thin films on DSSC performance. The crystal structure of Ti-Cu doped ZnO thin film was characterized using X-Ray diffraction (XRD) to determine the effect of annealing temperature on the quality of its crystal structure. XRD results show that the crystal structure is dominant in the (101) plane, with lattice parameters in the crystal tending to be constant at a = b = 5.21 and c = 3.25 so that the crystal volume tends to be constant at 47.77 Ã…. Furthermore, the FWHM value tends to decrease from 0.4419o to 0.2523o, crystal size tends to increase from 19.76 nm to 34.60 nm, dislocation density decreases from 0.0025 nm-2 to 0.0008 nm-2, stress decreases from 0.58% to 0.33%, and strain tends to increase from -1.364 GPa to -0.782 GPa. This indicates an improvement in crystal structure along with the addition of an annealing temperature of 350oC - 550oC. The SEM results showed that an annealing temperature of 450oC is a good temperature compared to other film variations, as evidenced by the agglomeration's narrowing and the grain size decrease.